Plasma oxidant/antioxidant status in period from the day of ovulation until embrional fixation day of pregnancy in mares - Nurettin Aydilek; M. Osman Atlı; Hayrettin Çetin; Hüdai İpek (Eurasian Journal of Veterinary Sciences)
This study was conducted to investigate plasma estradiol 17f3 and progesteron profiles, oxidant/ antioxidant status and the relationship among these parameters during the period Irom the day of ovulation until emb-rional lixation day in mares. Blood samples were collected on the day of ovulation (d=0) and on days 5, 10. and 16 ol pregnancy in 12 purebred mares. Plasma was analyzed for oxidant (ma I ond i aldehyde, index ol lipid peroxidation) and antioxidants (Vitamin E, (3-carotene, glutathione, catalase, glutathione peroxidase) values. Estradiol 17(3 level decreased after ovulation while, progesteron level gradually increased (p<0.05). Plasma malondialdehyde level on days 5 and 16 of pregnancy significantly were higher than d 0 (p<0.05). Plasma antioxidant parameters except for vitamin E gradually increased and this increase on 16th day was significantly higher than on day of ovulation day. Moreover, a negative correlation was observed (r=-0.50) between the plasma estradiol 17R and malondialdehyde concentrations. In conclusion, plasma malondialdehyde level generally increased, however the concentrations of 0-carotene, glutathione and activities of glutathione peroxidase and catalase parallelly increased during the period from the day ol ovulation until embrional fixation day in mares.